870000 STATE OF THE STATES (Tufts Archival Research Center, 2007)
Report which documents the political and economic climate with regard to the tobacco industry in each of the fifty states. Looks at the tobacco industry's resources to address legislation in the states for the year 1987. Summarizes their position and then lists their strengths and weaknesses in that state. Identifies allies and opposition as well.